Effectiveness and Safety of Tildrakizumab in Psoriasis Patients Who Failed Anti-IL17 Treatment: A 28-Week Real-Life Study - Megna M; Ruggiero A; Tommasino N; Brescia C; Martora F; Cacciapuoti S; Potestio L (Dove Medical Press, 2024)
Matteo Megna,* Angelo Ruggiero,* Nello Tommasino, Claudio Brescia, Fabrizio Martora, Sara Cacciapuoti, Luca Potestio Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy*These authors contributed equally to this workCorrespondence: Luca Potestio, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Napoli, 80131, Italy, Tel +39 - 081 - 7462457, Fax +39 - 081 - 7462442, Email potestioluca@gmail.comAbstract: Tildrakizumab is a humanised IgG1/k-type monoclonal antibody that targets the p19 protein subunit of IL23. Despite its effectiveness and safety have been widely reported by clinical trials and real-life experiences, data regarding its use on patients who previously failed anti-IL17 (brodalumab, ixekizumab, bimekizumab and/or secukinumab) are scant. Therefore, further studies on this topic would be beneficial for clinicians in guiding the selection of biologic shifting, considering that anti-IL23, − 12/23, and -IL17 partially share their therapeutic targets. In this context, we performed a 28-week, single-center, real-life, retrospective study, with the aim of assessing the efficacy and safety of tildrakizumab in patients who previously failed anti-IL17, also focusing the attention on psoriasis located in difficult-to-treat areas (scalp, palms or soles, fingernails, genitals). A total of 23 patients (12 male, 52.2%; mean age 52.8 ± 12.4 years) were enrolled. Of these, 11 (47.8%) failed secukinumab, 7 (30.4%) ixekizumab, 3 (13.0%) brodalumab, 1 (4.3%) both secukinumab and ixekizumab and 1 (4.3%) bimekizumab. At baseline, mean PASI and BSA were 12.8 ± 5.9 and 18.7 ± 9.6, respectively. At W16 PASI75 and PASI90 response were achieved by 15 (65.2%), and 9 (39.1%) patients, respectively, whereas 19 (82.6%) and 13 (56.6%) subjects reached these scores at W28. One (4.3%) case of primary inefficacy and 1 (4.3%) case of secondary inefficacy were assessed. Finally, no severe adverse events were collected. Tildrakizumab seems to be a valuable option in selected patients with psoriasis unresponsive to anti-IL17, suggesting that prior exposure to biological therapies seem not directly affect its effectiveness.Keywords: Tildrakizumab, psoriasis, real-life, anti-IL23